Open Data for Economic Growth - World Bank (Washington, DC, 2014)
Many governments are pursuing open data policies. One of the key policy drivers has been to use open data to drive economic growth and business innovation. This paper examines the evidence for the economic potential of open data and concludes that, despite a variation in published estimates and some methodological difficulties, the potential is very large indeed. It reviews the latest data about companies using open data, and highlights four companies which did not exist ten years ago, which are driven by open data, and which are each now valued at around $1 billion or more. It discusses the five archetypical types of businesses using open data, and cites concrete examples of each, and discusses the types of data which are proving most likely to lead to widespread business adoption and innovation. It suggests that governments should see themselves not only as a Supplier of open data but also as a leader, catalyst and user of it. Finally, it makes some recommendations for policies and actions which governments could take to maximize the economic growth possible from their data.